Deciphering mechanisms of action of ACE inhibitors in neurodegeneration using Drosophila models of Alzheimer’s disease - Ghalayini, Judy; Boulianne, Gabrielle L. (Frontiers in Neuroscience, 2023)
Alzheimer’s disease (AD) is a devastating neurodegenerative disorder for which there is no cure. Recently, several studies have reported a significant reduction in the incidence and progression of dementia among some patients receiving medications that inhibit the renin angiotensin system (RAS). Why RAS inhibitors are beneficial in some AD patients and not others is unclear although it has been shown to be independent of their role in regulating blood pressure. Given the enormous and immediate potential of RAS inhibitors for AD therapeutics it is imperative that we understand how they function. Recently, studies have shown that RAS inhibitors are also effective in suppressing neuronal cell death and memory defects in Drosophila models of AD despite the fact that the renin angiotensin system is not conserved in flies. This suggests that the beneficial effects of RAS inhibitors may be mediated by distinct and as yet, unidentified mechanisms. Here, we discuss how the short lifespan and ease of genetic manipulations available in Drosophila provide a unique and unparalleled opportunity to rapidly identify the targets of RAS inhibitors and evaluate their therapeutic effectiveness in robust models of AD.